Répartition géographique potentielle et modélisation de la niche écologique d' Harrisonia abyssinica , une espèce d'arbre médicinale prioritaire au Bénin (Afrique de l'Ouest) - Ogougbé, Raïmantou Egbèyèmi; AGBO, Relique Ignace; AHAMIDE, BERNARD; Djego‑Djossou, Sylvie; DJEGO, Gaudence Julien (My University, 2022)
The modelling of the ecological niche of Harrisonia abyssinica in Benin made it possible to have a function of both parameters which predicts the probability of the presence of the species in their respective habitats. This study showed the current distribution of this species and its prediction for 2050. Species occurrence data records were combined with climatic and soil data in Maximum Entropy (Maxent), a species distribution modelling lgorithm, to evaluate the impacts of future environmental conditions (under CNRM-CM5 and HadGEM2-ES) on the species’ potential distribution in Benin. The result showed that the habitats which are currently very suitable to H. abyssinica are mainly located in those agro-ecological zones: Cotton zone of the center (V), Zone of the land of bars (VI), Zone of depression (VII) and the Zone of fisheries (VIII) covering an area of 5339.21 km2 (4.7%) of the Beninese national territory. CNRM-CM5 model showed a decrease of 510.07 km2 in the highly suitable area for the species and HadGES-ES model showed an increase of 791.79 km2. According to the two models, the classified forest of Lama is and will remain the single protected forest moderately suitable to the conservation of H. abyssinica in Benin.
Keywords: Harrisonia abyssinica · Distribution · Modelling and suitable habitat · Ecological niche